Endogenous fluctuations in the demand for education - Michael Neugart; Jan Tuinstra (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
Enrolment rates to higher education reveal quite large variation over time which cannot be explained by productivity shocks alone. We develop a human capital investment model in an overlapping generations framework that features endogenous fluctuations in the demand for education. Agents are heterogeneous in their beliefs about future wage differentials. An evolutionary competition between the heterogeneous beliefs determines the fraction of the newborn generation having a certain belief. Costly access to information on the returns to education induces agents to use potentially destabilizing backward looking prediction rules. Only if previous generations experience regret about their human capital investment decisions, agents will choose a more sophisticated prediction rule that dampens the cycle. Access to information becomes key for stable flows to higher education. - expectations ; human capital investment ; endogenous fluctuations ; intergenerational spill-overs evolutionary dynamics ; bifurcation analysis – – Einschreibungen an Fachhochschulen und Universitäten weisen starke zyklische Schwankungen auf, die nicht allein durch Produktivitätsschocks erklärt werden können. Es wird ein Humankapitalmodell mit überlappenden Generationen vorgestellt, das die Eigenschaft besitzt, Zyklen in der Nachfrage nach Bildung endogen zu erklären. Im Modell sind die Akteure heterogen in Bezug auf ihre Voraussagen über zukünftige Lohndifferentiale. Ein evolutionärer Wettbewerb unter den Voraussagemethoden bestimmt den Anteil der Akteure, der ein bestimmtes Prognoseinstrument verwendet. Da der Zugang zu Informationen über zukünftige Humankapitalrenditen mit Kosten verbunden ist, weichen die Akteure auf vergangenheitsorientierte Voraussagemethoden aus, die destabilisierend wirken können. Nur dann, wenn frühere Generationen die Art und Weise wie sie prognostizierten bereuen, werden die Akteure kompliziertere, zukunftsgerichtete, Prognoseinstrumente wählen, welche die Zyklen dämpfen. Damit werden leicht verfügbare Informationen über Arbeitsmarktentwicklungen zur Schlüsselvariablen für konstante Zugänge zu Fachhochschulen und Universitäten, aber auch anderen Bildungsträgern.
Keywords: C60; E32; J24; 330; Bildungsverhalten; Berufswahl; Cobweb; Bildungsinvestition; Overlapping Generations; Arbeitsmarktprognose; Prognoseverfahren; Theorie